WLE/IWMI research influenced Ethiopian water sector policy reform to recognize multiple water values and other up-to-date options, benefitting irrigators, domestic and industrial users, and environment - CGIAR Research Program on Water, Land and Ecosystems (2020)
The Ethiopian Government has initiated a process of water policy reform. WLE/IWMI was approached by the Ministries of Agriculture and of Water, Irrigation, and Electricity to contribute to the review. Drawing from its research, WLE/IWMI brought new ideas to the policy reform table. These ideas include the concept of multiple water values; payment for ecosystem services; irrigation cost recovery, and irrigation performance benchmarking. These options have been incorporated in the draft policy document and will strengthen climate change adaptation.